2009
DOI: 10.1098/rstb.2009.0173
|View full text |Cite
|
Sign up to set email alerts
|

A model linking immediate serial recall, the Hebb repetition effect and the learning of phonological word forms

Abstract: We briefly review the considerable evidence for a common ordering mechanism underlying both immediate serial recall (ISR) tasks (e.g. digit span, non-word repetition) and the learning of phonological word forms. In addition, we discuss how recent work on the Hebb repetition effect is consistent with the idea that learning in this task is itself a laboratory analogue of the sequence-learning component of phonological word-form learning. In this light, we present a unifying modelling framework that seeks to acco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
242
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(255 citation statements)
references
References 62 publications
12
242
1
Order By: Relevance
“…More specifically, the Hebb effect reflects a form of longterm learning that results in unified representations of lists, or sub-sequences in lists, akin to the learning of words by forming unified representations of sequences of phonemes or letters (Page & Norris, 2009). Converging evidence supports the close link between the Hebb effect and word learning: The size of the Hebb effect correlates with individual differences in the ability to learn new word forms (Mosse & Jarrold, 2008;Szmalec, Loncke, Page, & Duyck, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…More specifically, the Hebb effect reflects a form of longterm learning that results in unified representations of lists, or sub-sequences in lists, akin to the learning of words by forming unified representations of sequences of phonemes or letters (Page & Norris, 2009). Converging evidence supports the close link between the Hebb effect and word learning: The size of the Hebb effect correlates with individual differences in the ability to learn new word forms (Mosse & Jarrold, 2008;Szmalec, Loncke, Page, & Duyck, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…There was no evidence of learning in this condition. On the basis of their results, Cumming et al (2003) as well as Hitch et al (2005) argued that Hebb learning consists of the formation of a unified (chunked) representation of the list, or at least of segments of the list (for computational models implementing this idea see Burgess & Hitch, 2006;Page & Norris, 2009). The acquisition and use of such chunks is disrupted if repetition is limited to sub-components of learned chunks.…”
Section: Asked Participants Inmentioning
confidence: 99%
See 1 more Smart Citation
“…The paired-associate learning paradigm differs from the Hebb effect because it involves explicit learning, a conscious intention to learn (Ellis, 1994;Hulstijn, 2001). Nevertheless, it has been suggested that the sequencelearning mechanism tapped experimentally in the Hebb repetition paradigm supports word learning generally (Page & Norris, 2009;Szmalec, Duyck, Vandierendonck, Mata, & Page, 2009). Mosse and Jarrold (2008) employed an adapted version of the paired-associate task involving word-picture and nonword-picture pairs in their group of typically developing 5-to 7-year-olds.…”
mentioning
confidence: 99%
“…In other words, existing long-term knowledge is a potential constraint on working memory performance. Conversely, working memory may serve as a mental workspace, allowing for the temporary maintenance of information that can be bound together into learnt, longer-term representations (see Baddeley, Gathercole, & Papagno, 1998;Page & Norris, 2009). …”
Section: Working Out Howmentioning
confidence: 99%